Pengaruh Beauty Influencer, Gaya Hidup, Dan Label Halal Terhadap Keputusan Pembelian Produk Cushion Somethinc (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Syiah Kuala) - Fadilla, Dina; Indriyani Sitepu, Novi (Fakultas Ekonomi dan Bisnis Islam, 2021)
The large population of Indonesia's Muslim community and many people who have accessed the internet as much as 62.10 percent are used by many beauty companies in marketing and selling products using beauty influencer marketing strategies. Data from the State of Global Economic Report 2021-2022 in the field of medicines and cosmetics, Indonesia is ranked ninth. This is in accordance with Indonesia's commitment to become the center of the sharia economy in 2024, which now Indonesia is ranked fourth in the world. Therefore, the production of local Indonesian products must be increased. Somethinc is a local brand that is currently popular in Indonesia. This study aims to analyze the influence of Beauty Influencers, Lifestyle, and Halal Labels on purchasing decisions for Cushion Somethinc products. This study uses a quantitative method using a Likert scale. The sample for this study were students of the Faculty of Economics and Business at Syiah Kuala University who used the Cushion Somethinc product. A total of 110 respondents were taken through a proposive sampling using the Hair formula. The analytical method used is multiple regression analysis. The results of this study indicate that Beauty Influencers, Lifestyle, and Halal Labels have a positive and significant effect on the decision to purchase cushion Somethinc products..